Ensino de ciências naturais, livros didáticos e imagens: investigando representações de gênero - Dias, Zaida Barros (2014)
The research Teaching Natural Sciences, Textbooks and Images: Investigating Representations of Gender reported on this thesis has the objective of analizing the gender representations on the images of Science textbooks from 6 ° to 9 ° grade of elementary school. The books while pedagogical resources used by teachers contribute to the conveyance and construction of knowledge and can influence the formation and transformation of student´s identity. The Images choice draws upon the understanding that they convey representations, discourses, practices, behaviors, lifestyles that contribute to the formation of gender identities. The gender is conceived as a social, cultural and historical framing,as proposed by Scott; representations as a way of knowledge that reveal values, beliefs and interpretations of an object (Moscovici) and speeches as practices which involve relations of power and production of knowledge (Foucault). The images were located in eight defined axes based on the incidence of human figures in situations conected to science, work, tecnological devices, body, sexuality, family and social interaction. The axes´analysis allowed the observation that the images, mostly permeate discourses linked to biological constitution of men and women, disregarding historical, social and cultural framing to build up identities. The gender is used to reinforce the dicotomy between men and women imposing them standards and behaviours, promoting and strengthening the inequality in gender relations in different areas and segments of society. These findings show that the textbooks surveyed, currently disregard not only the social transformations but also the changes related to gender, contributing therefore to the maintenance of prejudices and stereotypes. Therefore, it is necessary to be more critical regarding the images conveyed on science textbooks so as to have the possibility of analising the contents that support the ideas of differences and prejudices among genders shown on these images